Never let me go - Ishiguro, Kazuo (Faber and Faber, 2006)
In one of the most acclaimed novels of recent years, Kazuo Ishiguro imagines the lives of a group of students growing up in a darkly skewed version of contemporary England. Narrated by Kathy, now thirty-one, Never Let Me Go dramatises her attempts to come to terms with her childhood at the seemingly idyllic Hailsham School and with the fate that has always awaited her and her closest friends in the wider world. A story of love, friendship and memory, Never Let Me Go is charged throughout with a sense of the fragility of life.